The Influence of Identity Within-Person and Between Behaviours: A 12-Week Repeated Measures Study - Kristie-Lee R. Alfrey; Matthew Condie; Amanda L. Rebar (Behavioral Sciences)
People act in ways that align with the values and roles that constitute their identity. However, the consistency of identity’s influence across different behaviours, and whether identity influences behaviours directly or indirectly via intention, self-determined motivation, or habit, remains uncertain. Participants (N = 98; Mage = 30.4 years, SD = 11.7 years) completed up to 12 weekly surveys, self-reporting engagement in physical activity, student, and support-seeking behaviours, and behaviour-associated identity, intention strength, self-determined motivation, and habit. Stepwise multilevel models tested the between- and within-person associations of identity with behaviour, and whether the relationships remained after accounting for intention, self-determined motivation, and habit. Results suggested identity as stable, with the most variability at the between-person level. Identity was associated with behaviour at both within- and between-person levels, with the exception that support seeking and identity were only associated between-person. For student behaviour and physical activity, the identity–behaviour relationship at the within-person level waned and became non-significant after accounting for intention, but not self-determined motivation or habit. These findings highlight that identity may be difficult to change. However, as identity is associated with a range of behaviours, a person’s identification with a particular behaviour may be valuable for tailoring behaviour change interventions, specifically through or in the same way as behavioural intentions.